Bank- specific determinants of liquidity risk for commercial banks in Algeria: Panel data analysis during 2005-2020 - Fatma Benchenna (Financial Markets, Institutions and Risks)
This study aims to monitor a group of factors that cause liquidity risks and contribute to the occurrence of liquidity problems by testing the determinants of liquidity risk and the explanatory factors of the liquidity problem in Algerian commercial banks. This study seeks to highlight the importance of commercial banks' liquidity in financing investments to generate profits and the need to maintain appropriate levels to meet liquidity needs. Using panel data for a sample of nine Algerian banks during the period 2005–2020, the study found that the explanatory variables of the liquidity risks that cause liquidity problems in Algerian commercial banks by using the liquid assets to total assets index ratio are: return on assets, return on equity, and capital adequacy ratio, with an explanatory capacity of 59.44%. Analysis of the results of the fixed effect model showed an inverse correlation between the return on assets and liquidity risks. There was a statistically significant positive relationship between the return on equity, capital adequacy ratio, and liquidity risk. There was a negative, but not statistically significant, relationship between bank size, the loan loss provisions to total loans ratio, and liquidity risk. The study recommends that to increase the volume of assets, there should be a corresponding increase in liquid assets as a precaution against liquidity risks in Algerian banks. Also, other determinants are not addressed in the study, which requires further research into the determinants of liquidity risk in Algerian banks.